A functional paradigm for evaluating culture: An example with cetaceans - Alison Linda GREGGOR (Current Zoology, 2012)
Nonhuman culture was first considered in nonhuman primates because they are genetically similar to humans. However, evolution is not progressive and therefore many species may occupy niches that favor socially transmitted, group specific behavior. Not surprisingly, evidence for culture has accrued in several taxonomic groups, including cetaceans. If culture is an adaptation, it is imperative we understand the factors that favor its formation. Understanding the evolutionary origin of culture will allow for a wider range of species to be studied, including those that are difficult to test in the laboratory. I propose a broad-based functional paradigm for evaluating nonhuman culture; based on the idea that while not all cultural behaviors may garner fitness benefits to the individual, the ecological and social environments in which cultural behaviors evolved must have favored the physical attributes and social learning capabilities that allow for cultural formation. Specifically this framework emphasizes the relationships between social learning, ecology, social systems, and biology in relation to culture. I illustrate the utility of the functional paradigm with evidence from the ceteacean group, while setting the stage for a stringent species by species analysis. By means of contextualizing culture, the Functional Paradigm can evaluate a species’ potential to exhibit culture and can investigate potentially cultural behaviors [Current Zoology 58(2) : 271-286, 2012].